Analisis sampah domestik mahasiswa Universitas Sultan Ageng Tirtayasa (UNTIRTA) - Enggar Utari; Assyifa Rifdah Luthfiana; Indah Nazulfah (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Waste is something that is not used by humans that comes from an activity and production process, whether on a household scale, industry, mining and so on. This type of waste consists of organic waste derived from the remains of living organisms that can be decomposed. Meanwhile, inorganic waste comes from non-living organisms and cannot be decomposed. The purpose of this study was to determine the type of waste and the amount of waste in Biology Education students at Sultan Ageng Tirtayasa University who live in dormitories and boarding houses.. This research uses quantitative description method. Collecting data using questionnaires distributed to 20 people student. The results of the study showed that the total amount of organic and inorganic waste was 12,555.29 grams consisting of 2,525.73 grams or 20% organic waste and 10,030.3 grams or 80% inorganic waste. The most common types of organic waste are tissue, vegetable waste and food scraps. The most common types of inorganic waste are plastic, paper, styrofoam, and plastic bottles. The conclusion is that inorganic waste is more than organic waste.